A Survey of Wuat Wa’i Ritual Culture As Solidarity Value Of Golo Lebo Community - Sriwahyuni; Muh. Reski Salemuddin; Arfenti Amir; Abdul Malik Iskandar; Jalal (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2022)
Pesta sekolah or known wuat wa’I ritual is a form to support and the togetherness from the Manggarai community to help others who have difficulties in funding their son and girl in education. The purpose of this research is to find out why the wuat wa’I ritual culture has been survive until now in Golo Lebo Village. The research used qualitative type in a descriptive approach. Determination of informants in this study using snowball sampling technique. The symbol used during the event (prayer) is to slaughter a white chicken as an offering. The meat was eaten together and the inside is put in a container and then given to the ancestors as a symbol that they are also present at the ceremony and always guide the prospective nomad, and that hope can be symbolized by the expression lalong bakok du lakom lalong rombeng du kolem which means to go with a hope that the return will bring success. And if they finished college later, a thanksgiving event will also be held by slaughtering a black chicken as an expression of gratitude and gratitude to God and the ancestors who had protected and guided them while completing their studies in out of their land. In wuat wa'i ritual in an attitude of solidarity is manifested which is not hindered by certain forms of diversity. All community groups are present together to help the parties concerned. As conclusion that Wuat wa'i is very well known by the wider community in Manggarai. Because it is not told orally and handed down from generation to generation, but all people, from young children to adults are always involved in the wuat wa'i event.